Discrete Geometry for Computer Imagery 16th IAPR International Conference, DGCI 2011, Nancy, France, April 6-8, 2011, Proceedings - Debled-Rennesson, Isabelle; Domenjoud, Eric; Kerautret, Bertrand; Even, Philippe (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2011)
This book constitutes the refereed proceedings of the 16th IAPR International Conference on Discrete Geometry for Computer Imagery, DGCI 2011, held in Nancy, France, in April 2011. The 20 revised full papers and 20 revised poster papers presented together with 3 invited lectures were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on models for discrete geometry, discrete and combinatorial topology, geometric transforms, discrete shape representation, recognition and analysis, discrete tomography, morphological analysis, as well as discrete and combinatorial tools for image segmentation and analysis.